Evaluasi Metode Pembelajaran Melalui Kegiatan Bernyanyi Dalam Upaya Meningkatkan Kosa Kata Anak Usia Dini - Imran, Ranny Fitria; Haryono, Mimpira; Nurwita, Syisva (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to evaluate the effectiveness of singing-based learning methods in improving the vocabulary of early childhood children at Pembina Negeri 1 Kindergarten in Bengkulu City. The research method used a descriptive qualitative approach, with observation, interviews, and documentation as data collection techniques. The results showed that singing activities significantly improved children's vocabulary mastery. Children appeared more active, confident, and able to use new vocabulary in everyday communication. These findings align with Vygotsky's theory on the importance of social interaction in language development. In conclusion, singing is an effective, enjoyable learning method that is appropriate for the characteristics of early childhood language development.